Bois noir management in vineyard: a review on effective and promising control strategies - Pierro, Roberto; Moussa, Abdelhameed; Mori, Nicola; Marcone, Carmine; Quaglino, Fabio; Romanazzi, Gianfranco (Frontiers in Plant Science, 2024)
Among grapevine yellows, Bois noir (BN), associated with 'Candidatus Phytoplasma solani', represents the biggest threat in the main wine-growing areas worldwide, causing significant losses in berry quality and yields. BN epidemiology involves multiple plant hosts and several insect vectors, making considerably complex the developmentdeveloping of effective management strategies. Since application of insecticides on the grapevine canopy is not effective to manage vectors, BN management includes an integrated approach based on treatments to the canopy to make the plant more resistant to the pathogen and/or inhibits the vector feeding, and actions on reservoir plants to 2 reduce possibilities that the vector reaches the grapevine and transmit the phytoplasma. Innovative sustainable strategies developed in the last twenty years to improve the BN management are reviewed and discussed.